Zuma Modified Maneuver as a Treatment to Geotropic Lateral Semicircular Canal Benign Paroxysmal Positional Vertigo - Ramos, Bernardo Faria; Cal, Renato; Brock, Camila Martins; Mangabeira Albernaz, Pedro Luiz; Zuma e Maia, Francisco (International Archives of Otorhinolaryngology, 2020)
Introduction Benign Paroxysmal Positional Vertigo (BPPV) is the most common vestibular disorder, resulting from detached otoliths that migrate to one of the semicircular canals – canalolithiasis – or one of the cupulas – cupulolithiasis. The present study is related to lateral canal BPPVs, which may be either geotropic or apogeotropic. The geotropic variant of lateral semicircular canal benign paroxysmal positional vertigo (LC-BPPV) is attributed to free floating particles in the posterior arm of the lateral semicircular canal.Objectives To verify the possibility of employing the Zuma repositioning maneuver, with a brief modification, as an alternative treatment for geotropic LC-BPPV.Methods Seven patients with geotropic LC-BPPV were enrolled and treated with the Zuma modified maneuver. Patients were reevaluated 1 hour after a single maneuver, to confirm the resolution of vertigo and positional nystagmus.Results All seven patients achieved immediate resolution of vertigo and positional nystagmus as measured 1 hour after the application of the maneuver.Conclusion The Zuma modified maneuver was effective for geotropic LC-BPPV after a single application. The use of the Zuma maneuver for both apogeotropic and geotropic LC-BPPV may simplify the treatment of these patients.
Keywords: geotropic lateral canal benign paroxysmal positional vertigo; vertigo; repositioning maneuver